Isolation and identification of a morpholine-degrading bacterium - Cech, J S; Hartman, P; Slosárek, M; Chudoba, J (Applied and environmental microbiology, 1988)
A gram-positive, slowly growing rod effectively utilizing morpholine as the sole source of organic carbon, nitrogen, and energy was isolated from a mixed culture in a laboratory reactor. The strain was tentatively identified as Mycobacterium aurum. Its growth characteristics at 20 degrees C and pH 6.5 were as follows: maximum specific growth rate, 0.052 h-1; half-velocity constant, 1.3 mg/liter; and yield, 0.37 g/g. The optimum temperature and pH were 31 degrees C and 6.0, respectively.
Keywords: kinetika; Biodegradation, Environmental; biodegradace; Water Microbiology; Temperature; mikrobiologie vody; Morpholines; Mycobacterium; teplota; Kinetics; morfoliny